2007
DOI: 10.1128/jb.00246-07
|View full text |Cite
|
Sign up to set email alerts
|

The Quorum-Sensing Molecule Autoinducer 2 Regulates Motility and Flagellar Morphogenesis in Helicobacter pylori

Abstract: The genome of the gastric pathogen Helicobacter pylori contains a homologue of the gene luxS, which has been shown to be responsible for production of the quorum-sensing signal autoinducer 2 (AI-2). We report here that deletion of the luxS gene in strain G27 resulted in decreased motility on soft agar plates, a defect that was complemented by a wild-type copy of the luxS gene and by the addition of cell-free supernatant containing AI-2. Many bacterial species regulate aspects of their behavior through an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
97
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 53 publications
(65 reference statements)
6
97
2
Order By: Relevance
“…This result is consistent with the recent finding that in the oral bacterium Aggregatibacter actinomycetemcomitans, AI-2 regulates its biofilm formation most likely through its QseBC system (Shao et al, 2007). Also, in the human gastric pathogen Helicobacter pylori, AI-2 controls motility by controlling genes upstream of the motility and flagellar regulator FlhA (Rader et al, 2007). Further proof that AI-2 controls motility in different genera is that AI-2 regulates transcription of the flagellin gene, flaA, in the human pathogen Campylobacter jejuni (Jeon et al, 2003).…”
Section: Introductionsupporting
confidence: 81%
“…This result is consistent with the recent finding that in the oral bacterium Aggregatibacter actinomycetemcomitans, AI-2 regulates its biofilm formation most likely through its QseBC system (Shao et al, 2007). Also, in the human gastric pathogen Helicobacter pylori, AI-2 controls motility by controlling genes upstream of the motility and flagellar regulator FlhA (Rader et al, 2007). Further proof that AI-2 controls motility in different genera is that AI-2 regulates transcription of the flagellin gene, flaA, in the human pathogen Campylobacter jejuni (Jeon et al, 2003).…”
Section: Introductionsupporting
confidence: 81%
“…This confirms that the loss of AI-2 rather than the loss of metabolic or regulatory LuxS functions were responsible for these effects [47]. Rader et al [46] determined that AI-2 functions as signalling molecule up-stream of the flagellar regulator flhA in H. pylori. These data suggest that bacterial motility or flagella formation and function in C. jejuni is dependent on a functional luxS but not AI-2 at 37 °C while in H. pylori it is partially under control of AI-2.…”
Section: Motility and Chemotaxissupporting
confidence: 61%
“…Only Holmes et al [43] complemented the luxS mutant by the addition of exogenously produced AI-2 but observed no restoration in gene expression or motility, and concluded that these effects were due to deletion of luxS and not of AI-2 depletion. The luxS mutants of the H. pylori strains X47-2AL and Alston did not show any obvious defects compared to corresponding wild type strains [39,44], while motility of other H. pylori luxS mutants of the strains TK1402, G27, SS1 and J99 was reduced as observed in soft agar motility assays and by microscopy [44][45][46][47]. In contrast, no differences in flagella formation were detected using scanning electron microscopy [45,46].…”
Section: Motility and Chemotaxismentioning
confidence: 81%
See 1 more Smart Citation
“…In the case of E. coli, this could be the gastrointestinal tract of vertebrates and/or the external environment. Finally, as AI-2 has been reported to regulate the motility of other bacteria such as Campylobacter jejuni and Helicobacter pylori as well (Elvers and Park, 2002;Rader et al, 2007), this active grouping behavior might not be restricted to E. coli and might add yet another dimension to microbial ecology.…”
mentioning
confidence: 99%